2006
DOI: 10.1139/x06-003
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and parentage analysis of black poplar along the Morava River

Abstract: Twelve nuclear microsatellite markers were used to assess the population genetic structure of the riparian pioneer tree species Populus nigra L. along the Morava River in the Czech Republic. Parentage analysis of 30 seedlings was performed to examine the extent of hybridization between P. nigra and introduced hybrid poplars and to determine the distances of pollen and seed movement. Additionally, spatial genetic structure was analysed and gene dispersal was estimated indirectly. In spite of the limited size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 43 publications
10
36
2
4
Order By: Relevance
“…1), which is in agreement with previous genetic studies of Populus nigra employing a variety of genetic marker systems [13][14][15][16][17][18]. All nSSR loci were highly polymorphic.…”
Section: Resultssupporting
confidence: 90%
“…1), which is in agreement with previous genetic studies of Populus nigra employing a variety of genetic marker systems [13][14][15][16][17][18]. All nSSR loci were highly polymorphic.…”
Section: Resultssupporting
confidence: 90%
“…Because of the high exclusion power needed for parentage analysis (Marshall et al 1998), studies on seed dispersal in literature are few. There is only one other study on explicit seed dispersal estimation for P. nigra (Pospísková & Sálková 2006). Within a small population along the Morava river, they found seed dispersal distances ranging from 163 to 370 m. The difference in respect to our results may be due to the small scale of their investigation.…”
Section: Gene Flow Assessment By Molecular Techniquescontrasting
confidence: 99%
“…Tabbener & Cottrell (2003) for P. nigra found pollination distances between 25-350 m and DiFazio et al (2004) reported mean pollination distances for Populus trichocarpa between 140-1100 m, with a strong dependency on the area sampled. This finding have been confirmed by Pospísková & Sálková (2006), who found effective pollination distances of 10-230 m within a population of 65 adult trees and 30 analyzed seedlings of P. nigra along the Morava river.…”
Section: Gene Flow Assessment By Molecular Techniquessupporting
confidence: 58%
“…For over 30 % of individuals from the studied population, full-sibling relationships were inferred, which strongly suggests the predomination of within-population crossings and recruitment events. Based on parentage analysis, Pospíšková and Šálková (2006) indicated domination of within-population pollinations in studied black poplar stands-77 % of offspring were fathered by males from the local population.…”
Section: Discussionmentioning
confidence: 97%